Efek Penggunaan Water Mist Terhadap Tekanan, Temperatur dan Kinerja Sistem Mesin Pengkondisian Udara Tipe Terpisah - Azridjal Aziz; Bungsu Herwanto; Rahmat Iman Mainil (METAL: Jurnal Sistem Mekanik dan Termal, 2020)
The air conditioning machine commonly used is air conditioning system with a vapor compression cycle. The use of air conditioning machines consumes more electrical energy than other household appliances. In this study, the addition of the water mist method in evaporative cooling system with variations of distance of 20 cm, 40 cm, 60 cm so that the energy consumption of split type AC (Air Conditioning) of machines is more efficient. The results showed that the pressure of the condenser using water mist was lower 48 Psig than the pressure of condenser with a cooling load of 2000 W, and lower by 34 Psig of the pressure of condenser without the cooling load. Meanwhile the temperature of the air entering the condenser (Tout) after using a water mist has lower temperature than without the water mist, therefore it can save electricity consumption in the compressor. The temperature of the lowest inlet air of the condenser reached at the use of water mist with a distance variation of 60 cm was 28 ℃. And the relative humidity (RH)  relatively decrease at the exit  of the condenser using water mist with distance variation of 60 cm length was 59.6%. The compressor power decreased lower using a 60 cm distance water mist of 0.52 kW compared to without using a water mist with a 2000 W load of 0.56 kW. So that COP using water mist higher about 5.24 than without a water mist of 4.72. The highest COP was obtained using water mist at a distance of 60 cm